Magnetically recoverable multifunctional ZnS/Ag/CoFe2O4 nanocomposite for sunlight driven photocatalytic dye degradation and bactericidal application. (March 2020) - Palanisamy, G.; Bhuvaneswari, K.; Chinnadurai, A.; Bharathi, G.; Pazhanivel, T.
Abstract: Sunlight driven photocatalysis is the next step of environmental remediation, which can utilize the renewable energy to cure environmental problems. Herein we report a magnetically recoverable ZnS/Ag/CoFe2 O4 nanocomposite photocatalyst for sunlight driven photocatalytic dye degradation. The composition, structure, morphology, magnetic and photophysical properties of the as prepared samples were investigated by a wide range of characterization methods. The ZnS/Ag/CoFe2 O4 nanocomposite demonstrated sunlight driven photocatalytic activity towards the degradation of two different organic dye pollutants. The radical scavenging tests were conducted to examine the role of different radicals in degrading the dye pollutants. With demonstrated ferromagnetic behavior, the ZnS/Ag/CoFe2 O4 nanocomposite was magnetically recoverable using a commercial bar magnet. The antibacterial activity of the nanocomposite were also examined against both G + (Staphylococcus aureus) and G − (Escherichia coli) bacteria's. Relatively, the ZnS/Ag/CoFe2 O4 nanocomposite showed better antibacterial activity as compared to CoFe2 O4 NPs and Ag/CoFe2 O4 samples. Graphical abstract: Image 1 Highlights: Magnetically recoverable ZnS/Ag/CoFe2 O4 nanocomposite photocatalyst were synthesized by simple wet precipitation method. ZnS/Ag/CoFe2 O4 nanocomposite exhibit high stability for successive cycles with enhanced photocatalytic performance against MB & RhB dyes. The antibacterial activity of the ZnS/Ag/CoFe2 O4 nanocomposite showed better antibacterial activity as compared to CoFe2 O4 NPs and Ag/CoFe2 O4 samples.